Analisis Tingkat Kualitas Pelayanan Nasabah Pegadaian Syariah Cabang Veteran Purwakarta - saepul Bahri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
Based on the results of the research and discussion on the Level of Quality Analysis of the Syariah Pawnshop Customer Service at the Veteran Purwakarta Branch, some conclusions can be drawn as follows: (1) From the physical evidence at the Pegadaian Syariah Branch Veterans Purwakarta the community considers that the condition of the building owned and the way employees are in look good enough, and the promotion carried out by the pawnshop can attract the public to transact at pawnshops; (2) The reliability of sharia pawnshops in conducting services on time is considered to be good enough, some customers are satisfied. In addition, sharia entrepreneurs also never break promises, and always try to help solve problems faced by their customers at the time of the transaction, and always be careful in recording data; (3) The responsiveness of sharia pawnshops is a willingness to assist and provide prompt and appropriate services to customers, with clear information delivery and willingness to welcome customers to be assessed by the Veteran Purwakarta Branch of Pawnshop customers as considered to be the most important and have the most dominant influence to increase customer satisfaction; (4) Guarantees and certainty given by the branch of Veterans Purwakarta sharia pawnshop, namely the trustworthy nature of employees, adequate knowledge of the problem of sharia pawnshop products, as well as the polite attitude of sharia pawnshop employees towards customers who wish to transact which the community values ​​are good; (5) Attention given by the Veteran Purwakarta branch pawnshop to sharia pawnshop customers get a good response. The customer considers that the pawnshop is able to provide convenience in conducting transactions, can understand the needs of its customers, and provide personal attention to its customers. Of the five service dimensions it is known that the dimensions of service that are considered the best according to respondents' perceptions are the Tangible dimension (physical evidence) which is 79%. While the assessment is low according to the respondent's perception that is in the dimensions of Reliability (reliability) that is equal to 76.5%.